EFFECTS OF SEGMENTATION OF INSTRUCTIONAL ANIMATION IN FACILITATING LEARNING - Mohamad Ali, Ahmad Zamzuri; Madar, Ahmad Rizal (Journal of Technical Education and Training, 2010)
The aim of this study was to investigate the effects of segmented-animation, playpause- animation and continuous-animation in facilitating learning of low prior knowledge learners. A courseware prototype entitled Transmission Media was developed for the research purpose. The courseware contains nine animations on various topics in Transmission Media. Pre-test and post-test experimental design was employed on three different groups respectively. The data collected were analyzed statistically by using one-way between-groups ANOVA with post-hoc comparisons. Apparently, the result suggests that segmented-animation was significantly more effective than play-pause-animation and continuous-animation in enhancing students’ learning performance. The result indicates that segmented-animation was beneficial for students in conducting adequate cognitive processes of the information depicted in the animation. Furthermore, the result shows that allowing students to decide the segmentation in play-pause-animation condition does not necessarily promotes better learning. This was due to low prior knowledge students’ inability in deciding the appropriate stop points in animation and/or play-pause-replay button design that might causes split attention effect resulting extraneous cognitive load throughout the learning process.